Doing Ethics in a Pluralistic World : Essays in Honour of Roger C. Hutchinson - Buss, Helen M. (Helen Margaret) (Comparative ethics series ;, 2002)
Doing Ethics in a Pluralistic World is an apt title for this collection of essays in honour of Roger C. Hutchinson who, over many decades, has encouraged and participated in shaping a Canadian contextual social ethics. His abiding interest in social ethics and in religious engagement with public issues is reflected in his life's work; seeking the consensus and self-knowledge required to achieve cooperation in the search for a just, participatory, and sustainable society. One of Roger Hutchinson's many notable accomplishments is his development of a method of dialogue for ethical clarification in situations of diversity. Some of the essays collected here apply this method to specific issues, while others discuss how religious persons and organizations can and do co-operate in a pluralistic world to achieve social and ecological well-being. All essays are of keen interest to those concerned with the role and function of ethics at the matrix of religious conviction and social transformation. For nearly three decades Roger Hutchinson has been based at Victoria University in Toronto, first in religious studies, then at Emmanuel College, where he completed his teaching career as professor of church and society while serving as principal from 1996 to 2001.